2022
DOI: 10.3390/foods11040524
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analysis of Halotolerant Staphylococcus saprophyticus Isolated from Korean Fermented Shrimp

Abstract: Saeu-jeotgal, a Korean fermented shrimp food, is commonly used as an ingredient for making kimchi and other side dishes. The high salinity of the jeotgal contributes to its flavor and inhibits the growth of food spoilage microorganisms. Interestingly, Staphylococcus saprophyticus was discovered to be capable of growth even after treatment with 20% NaCl. To elucidate the tolerance mechanism, a genome-wide gene expression of S. saprophyticus against 0%, 10%, and 20% NaCl was investigated by RNA sequencing. A tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Some bacterial strains were also considered pathogens because they colonize the human rectum and urogenital tract (Devi et al 2015). The S. saprophyticus strain found in jeotgal (a fermented shrimp product from Korea) was not pathogenic (Jo et al 2022). Porkfish as the raw material for inasua has a high protein content (>18%) (Đorđević et al 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Some bacterial strains were also considered pathogens because they colonize the human rectum and urogenital tract (Devi et al 2015). The S. saprophyticus strain found in jeotgal (a fermented shrimp product from Korea) was not pathogenic (Jo et al 2022). Porkfish as the raw material for inasua has a high protein content (>18%) (Đorđević et al 2016).…”
Section: Resultsmentioning
confidence: 99%
“…For instance, comparative transcriptomic and physiological analysis revealed that the halotolerant bacterium Egicoccus halophilus EGI 80432 T increased inorganic ions uptake and accumulated trehalose and glutamate in response to moderate salinity condition, while the high salt condition led to up-regulated transcription of genes required for the synthesis of compatible solutes, such as glutamate, histidine, threonine, proline, and ectoine ( Chen et al, 2021 ). The role of glutamate as a key compatible solute for halotolerance was also reported in a halotolerant strain of Staphylococcus saprophyticus based on transcriptome comparison of cells cultivated in media containing different concentrations of NaCl (0, 10, and 20%; Jo et al, 2022 ). In the exoproteome of the halotolerant bacterium Tistlia consotensis grown at high salinity, proteins associated with osmosensing, exclusion of Na + and transport of compatible solutes, such as glycine betaine or proline are abundant ( Rubiano-Labrador et al, 2015 ).…”
Section: Introductionmentioning
confidence: 86%
“…This disparity between treatments might be due to S. aureus's response to the sudden exposure of cold plasma in the early treatment (T1), where more RNA encode for stress proteins were generated than in the other treatments (T3 and T5). Other research revealed each stress protein can be regulated by different stress conditions, such as Gls24 family stress response protein, which can be induced by aerated conditions [29] and copper stress [30], and GlsB/YeaQ/YmgE family stress response protein, which is possibly related to butanol [31] and salt tolerance [32]. A total of six DEGs related to antioxidants were identified in cold plasma-treated S. aureus, all of which were upregulated (three in T1/T3/T5), please refer to (b) in Table 2.…”
Section: In-depth Comparative Analysis Of Degs Harbored From T1 T3 An...mentioning
confidence: 99%